Substituted group directed assembly of energetic lead(ii) compounds based on structure-relevant ligands. Issue 103 (6th October 2015) - Yang, Gao Wen; Zhang, Fei Fei; Wu, Qi; Cao, Meng Jie; Bai, Yu; Li, Qiao Yun; Wei, Bo; Zou, Jian Hua
Abstract : Two Pb(ii ) compounds were prepared. The luminescence properties were investigated. The DSC shows that compound2 can be used as a energetic material. Abstract : Reactions of two structure-relevant ligands, Hpytz [Hpytz = 5-(4-pyridyl)tetrazole] and its 2 H -tetrazole-carboxylate substituted derivative Hpytza [Hpytza = 5-(4-pyridyl)tetrazole-2-acetic acid] with Pb(NO3 )2 under the presence of potassium hydroxide, afforded a new mononuclear [Pb(pytz)2 (H2 O)4 ]·3H2 O (1 ) and a two dimensional polymer [Pb(pytza)2 ] n (2 ) with (4, 4) topology, respectively. The two compounds were characterized by elemental analysis, IR and single crystal X-ray diffraction. The luminescence properties of compounds1 and2 investigated at room temperature in the solid state show both intraligand emission and characteristic peak of Pb 2+ . Differential scanning calorimetry (DSC) and thermogravimetric-differential thermogravimetric (TG-DTG) analyses were applied to assess the thermal decomposition behavior of compounds1 and2 . The DSC test indicates that compound2 can be taken advantage of as a potentially explosive material.